2010
DOI: 10.3136/fstr.16.209
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Characteristics of Triacylglycerols and Phospholipids in Adzuki Beans (Vigna angularis)

Abstract: Fatty acid distribution of triacylglycerols and phospholipids isolated from five cultivars of adzuki beans (Vigna angularis) was investigated. Lipids were separated by TLC into eight subfractions. The lipid components comprised mainly phospholipids and triacylglycerols. The phospholipid components included phosphatidylcholine, phoshatidylinositol, and phosphatidylethanolamine. Comparison of these different cultivars showed, with a few exceptions, no significant differences in fatty acid distribution. Fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a previous work, two fatty acids were identified from PC of adzuki bean, namely, 16:0 and 18:2, which was the most abundant fatty acids (Yoshida, Yoshida, Tomiyama, & Mizushina, 2010). In our study, we have identified the same fatty acids, however, C18:1n9c was the most abundant one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work, two fatty acids were identified from PC of adzuki bean, namely, 16:0 and 18:2, which was the most abundant fatty acids (Yoshida, Yoshida, Tomiyama, & Mizushina, 2010). In our study, we have identified the same fatty acids, however, C18:1n9c was the most abundant one.…”
Section: Resultsmentioning
confidence: 99%
“…They accounted for 84.5% of total PC species. Several previous studies involved the determination of the fatty acid profiles of lipids including triacylglycerols and phospholipids from adzuki beans by GC analysis (Yoshida et al., 2010; Yoshida, Tomiyama, & Yoshida, 2010; Yoshida, Yoshida, & Tomiyama, 2008). However, GC analysis requires hydrolysis and derivatization of phospholipids, this procedure leads to loss the information about the chemical structure of the complete phospholipid molecules, while LC‐MS (liquid chromatography‐mass spectrometry) could provide the exact molecular structure information.…”
Section: Resultsmentioning
confidence: 99%
“…Oleic (C18:1), linoleic (C18:2), and linolenic (C18:3) acids were identified in the adzuki extract by the HPLC system described in Materials and Methods, and their concentrations in the extract were estimated to be 71.1 ± 12.8, 4.8 ± 1.4, and 3.6 ± 0.6 mM ( n = 3), respectively. Here, the concentration of oleic acid was much higher than that of linoleic acid, but it has been reported that the content of linoleic acid is greater than that of oleic acid in the adzuki bean [ 23 , 24 ]. Therefore, both oleic and linoleic acids were used here.…”
Section: Resultsmentioning
confidence: 99%